2007
DOI: 10.1152/jn.00876.2006
|View full text |Cite
|
Sign up to set email alerts
|

P1 and Traveling Alpha Waves: Evidence for Evoked Oscillations

Abstract: Klimesch W, Hanslmayr S, Sauseng P, Gruber WR, Doppelmayr M. P1 and traveling alpha waves: evidence for evoked oscillations. J Neurophysiol 97: [1311][1312][1313][1314][1315][1316][1317][1318] 2007. First published December 13, 2006; doi:10.1152/jn.00876.2006. The hypothesis is tested whether the P1 of the event-related potential (ERP) component behaves like an evoked, traveling alpha wave. This hypothesis is based on different kinds of evidence showing, e.g., that-after undergoing phase reorganization-freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 25 publications
6
68
2
Order By: Relevance
“…The ITC provides a measure for the degree of phase locking for a specific oscillation to a stimulus, and it has been shown that phase-locked oscillations might modulate ERP components (Klimesch et al, 2004;Hsiao et al, 2006;Klimesch et al, 2007;Rousselet et al, 2007;Freunberger et al, 2009). Furthermore, improved temporal coordination within and across task-related brain regions may be an important mechanism underlying fast and efficient behavioral performance (Ghuman et al, 2008;Gilbert et al, 2010).…”
Section: Results Of Intertrial Synchrony Analysismentioning
confidence: 99%
“…The ITC provides a measure for the degree of phase locking for a specific oscillation to a stimulus, and it has been shown that phase-locked oscillations might modulate ERP components (Klimesch et al, 2004;Hsiao et al, 2006;Klimesch et al, 2007;Rousselet et al, 2007;Freunberger et al, 2009). Furthermore, improved temporal coordination within and across task-related brain regions may be an important mechanism underlying fast and efficient behavioral performance (Ghuman et al, 2008;Gilbert et al, 2010).…”
Section: Results Of Intertrial Synchrony Analysismentioning
confidence: 99%
“…The time window for detecting peak amplitude of the P1 component was 50-150 msec (e.g., Klimesch, Hanslmayr, Sauseng, Gruber, & Doppelmayr, 2007). For visualization of ERPs, we applied a 30-Hz linear low-pass filter.…”
Section: P1 Event-related Potentialsmentioning
confidence: 99%
“…Phase shifts in potentials therefore have great potential for BMI. The informativeness of time lags is also supported by studies of vision (see, for example, [Klimesch et al, 2007]). In relation to brain-machine interfaces, the movement of LFP in the primary motor and dorsal premotor areas of the cortex has already been studied in monkeys in a "reaching task" [Rubino et al, 2006].…”
mentioning
confidence: 75%
“…Apart from the low spatial resolution of the EEG (as compared with LFP), the reason for this would appear to be that the spectral parameters used are indirectly related to the information processes of sensorimotor encoding. Movement of the potential wave is now believed to be directly related to encoding [Tsitseroshin and Shepoval'nikov, 2009;Ermentrout and Kleinfelt, 2001;Klimesch et al, 2007;Lopes da Silva, 1989;Lubenov and Siapas, 2009] and there are many reports of their links with motor functions and visual perception [Bark et al, 2005;Shevelev et al, 2002;Rubino et al, 2006;and others]. In particular, we cannot fail to note the often cited work of Nicolelis et al [Lebedev and Nicolelis, 2006;Nicolelis et al, 1995;Petermann et al, 2009] on sensorimotor encoding in hand movements in monkeys and in whisker movements in rats in conditions of free behavior.…”
mentioning
confidence: 99%